GENDER PROGRESSIVE TEACHING IN PREMARITAL COURSE: Study on Islamic Marriage Guidance Books for Prospective Muslim Couples - Marwah, Sitti (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2022)
For more than two decades, the government has been attempting to pay attention to gender equality in Indonesia. However, these efforts have not been claimed successful. This paper examines the contents of the marriage guidance book for bride and groom, initiated by the Office of Religious Affairs. This paper aims to analyze the concept of equality defined in the book. The primary source of this study is the marriage guidance book, which has been referred to by the Ministry of Religious Affairs: (1) The Marriage Guidance Module for Bride and Groom, and (2) The Sakinah Family Foundation Book. The data is also collected through interviews. The analysis was conducted using a gender approach, which is aimed at mapping the type of relationship between men and women within the family in the course book. After conducting research, it is found that the Ministry of Religious Affairs collaborated with a number of experts on gender equality in drafting the books. Therefore, the concept of gender equality between husband and wife presented in the books shows a progressive understanding.[Lebih dari dua dekade pemerintah telah berupaya memberikan atensi terhadap wacana kesetaran gender di Indonesia. Akan tetapi upaya tersebut belum begitu berhasil. Tulisan ini mengkaji tentang isi buku tuntunan perkawinan bagi calon pengantin yang digagas oleh Kantor Urusan Agama. Tulisan ini bertujuan untuk menganalisis konsep kesetaraan yang didefinisikan dalam buku tersebut. Sumber utama penelitian ini adalah buku pedoman perkawinan yang dirujuk oleh Kementerian Agama. Buku-buku tersebut adalah (1) Modul Bimbingan Nikah untuk Pengantin, dan (2) Buku Yayasan Keluarga Sakinah. Data tersebut juga dikumpulkan dengan wawancara. Analisis dilakukan dengan menerapkan pendekatan gender, yang bertujuan untuk memetakan bentuk relasi antara laki-laki dan perempuan dalam kursus perkawinan. Setelah melakukan penelitian, penulis menemukan bahwa Kementerian Agama bekerjasama dengan sejumlah pakar kesetaraan gender dalam penyusunan buku tersebut. Oleh karena itu, konsep kesetaraan gender antara suami dan istri yang disajikan dalam buku-buku tersebut menunjukkan pemahaman yang progresif.]